Experimental study on the effect of varying syngas composition on the emissions of dual fuel CI engine operating at various engine speeds - Mahgoub, B.K.M. (Institute of Physics Publishing, 2015)
Using syngas as a supplement fuel of diesel in dual fuel mode is a proposed solution in the effort to protect the environment and control the serious threats posed by greenhouse gas emissions from compression ignition engines. The objective of this study was to experimentally examine the effect of syngas composition on the exhaust emission of dual fuel compression ignition (CI) engine at various engine speeds, and to compare the operating ranges of imitated syngas versus pure diesel. The study was conducted using a naturally aspirated, two strokes, single cylinder 3.7 kW diesel engine operated at speeds of 1200, 2000 and 3000 rpm. The engine was tested with three different syngas compositions. Diesel fuel was partially substituted by syngas through the air inlet. The test results disclose the impact of using syngas in CI engines on emission of CO2, NOx, unburned hydrocarbons and carbon monoxide. The experimental measurements confirmed that all syngas compositions are capable of reducing the emissions of CO2 and NOX compared with diesel fuel. Wide range of diesel replacement ratios (up to 72) was attained without any penalty. Syngas with composition of 49 N2, 12 CO2, 25 CO, 10 H2, and 4 CH4 reduced the emissions of CO2 and NOx at engine speed of 1200 rpm up to 1 and 108 ppm, respectively. The lowest emission of UHC and NOx was emitted when the engine was operating at speed of 2000 rpm and 3000 rpm, respectively with composition of 38 N2, 8 CO2, 29 CO, 19 H2, and 6 CH4. Therefore, syngas could be a promising technique for controlling NOx emissions in CI engines. However, hydrogen content in syngas is important parameter that needs to be further investigation for its effect.